Non est mea pigra senectus: Old Women and Folk Medicine in Greco-roman Literature - Meseguer González, Diego (Acta Classica Universitatis Scientiarum Debreceniensis, 2021)
This paper will examine the old-woman healer figure through Greco-Roman literary sources. First, I will discuss briefly the social reputation of old women in comparison with senex and the creation of a negative stereotype around them. After that, I will focus on the triple relation between woman, old age, and medicine in order to show the reputation of old women as skilled healers. Finally, I will analyse the use of different treatments close to magic, like enchantments and purifications, and the healings of some specific illnesses, such as love, to conclude with a brief overview of the political and social attitude towards them.